Sistem Informasi Inventory Barang Menggunakan Metode Reorder Point Berbasis Java Pada LSP Ataknas Profesional Konstruksi - Safira Oktafiani; Rizki Ridwan; Rini Sriyanti (Politeknik Kampar, 2023)
The purpose of the research is to design and implement a Java-based Inventory Information System at LSP Ataknas Professional Construction. The research methodology used in the data processing system is data collection techniques such as interviews, observations, documentation studies, and conducting literature research relevant to the problem of the previous goods inventory system. The system development method used is the Re-Order Point method. The results of this study are the existence of an application tool created with the Java Netbeans programming language and data storage in the MySQL database can provide smooth processing of the Goods Inventory Information System system.